2003
DOI: 10.1046/j.1365-2265.2003.01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral parameters of oxidative stress in Graves’ disease: the effects of methimazole and 131 iodine treatments

Abstract: Our results confirm the imbalance of the antioxidant/oxidant status in hyperthyroid patients. MMI treatment was more effective than 131I therapy to improve that balance. We speculate on the benefits of antioxidant therapy administrated together with the habitual treatment of hyperthyroidism, especially in patients after 131I therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
1
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 38 publications
8
67
1
4
Order By: Relevance
“…In addition, the low success rate of radioiodine therapy under simultaneous carbimazole therapy in spite of comparable radioiodine uptake strongly argues against a radioiodine uptake-mediated detrimental mechanism of carbimazole. In this context, radioprotection by the inhibition of peroxidase-catalysed synthesis of oxygen free radicals, which mediate the cell damage in radioiodine therapy [10,11], appears to be a more likely mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the low success rate of radioiodine therapy under simultaneous carbimazole therapy in spite of comparable radioiodine uptake strongly argues against a radioiodine uptake-mediated detrimental mechanism of carbimazole. In this context, radioprotection by the inhibition of peroxidase-catalysed synthesis of oxygen free radicals, which mediate the cell damage in radioiodine therapy [10,11], appears to be a more likely mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Carbimazole decreases the peroxidase-catalysed synthesis of oxygen free radicals, which mediate the cell damage produced by radioiodine [10,11]. On the other hand, carbimazole reduces the cellular radioiodine uptake [3,5], which has also been thought to decrease the success of radioiodine therapy [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The selected drug directly inhibits the synthesis of thyroid hormones by interfering with iodine incorporation into tyrosyl residues of thyroglobulin, secondary to interfering with the oxidation of iodide ion and iodotyrosyl groups through inhibition of the peroxidase enzyme. The primary influence on hypothalamus/hypophysis axis was not revealed [1,27].…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of antioxidative defence is multifactorial. Many studies have indicated connections of iodothyronine hormones with oxidative stress [1,4,7,16,20]. NADPH 2 cytochrome P-450 reductase (P-450R), the main enzyme responsible for the doxorubicin-dependent free radical generation, is strictly regulated by triiodothyronine (T3) [8,17] and markedly decreased level of this enzyme (30-50%) was observed in heart of rats treated with methimazole [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…Подтверждением этого является обнаружение досто верно более высоких концентраций мочевого малон диальдегида (маркер оксидативного стресса) у паци ентов с БГ по сравнению с группой контроля [35]. К настоящему моменту имеются данные о том, что прием тиреостатиков (тиамазол или пропицил) у па циентов с БГ приводит к восстановлению окисли тельного баланса в тиреоцитах [1,68].…”
Section: селен и болезнь грейвсаunclassified